THE USE OF ENGLISH COMICS TO IMPROVE STUDENTS’ SPEAKING ABILITY BY STORYTELLING AT SECOND GRADE STUDENTS’ AT SMP N 8 BATANGHARI JAMBI IN ACADEMIC YEAR 2016/2017 - Gagar Marta Nugraha; Sri Marmoah; Erisa Kurniati (Universitas Batanghari Jambi, 2018)
The purpose of this research is to find out whether or not there is significant students’ speaking ability in storytelling (variable Y) use of English comics (variable X) in teaching storytelling at the second grade students’ of SMP N 8 Batanghari Jambi. This research is use quantitative method. This research is an experimental research. The population of this research are the second grade students of SMP N 8 Batangari Jambi consist of 79 students. The sample of the research are two classes which consist of 54 students. That is class VIII A consist of 27 students as control class and VIII B consist 27 students as experiment class by simple random sampling. The instrument used to collect data is story comic test form of multiple choice. Those are pre-test which is given before the treatment and post-test which is given after the treatment. There are four treatments for the sample, especially class VIII B. After the data is collected, the researcher used t-test analysis to see the difference between pre-test and post-test. The result of t-test is 2,41 is higher than t-table 2,00 with the of freedom (df) = 52 and level significance 0,05. So, the value of t-test was higher than the value of t-table, it can be concluded that the hyphothesis was accepted. Based on the finding, the reseacher concluded that use of English comic can be used to improve the students’ speaking ability by storytelling. Keywords: English Comic, Storytelling